Convergent Evaluation of Working Memory and Arithmetic Ability in a Child with Autism Spectrum Disorder without Intellectual Impairment - Pellizzoni, Sandra; Passolunghi, Maria C. (Frontiers in Psychology, 2017)
Studies focusing on a joint evaluation of both Working Memory (WM) and math ability (MA) in autism are far from abundant in literature, possibly due to inadequate methodological approaches and reported inconsistencies between results obtained in each separate field of research, resulting in contradictory conclusions. The specific aim of this case report is therefore evaluating and integrating results on these two cognitive abilities in a child with autism spectrum disorder without intellectual impairment. Our data on an autistic ten-year-old child (M.N.) show that the levels of functional (active vs passive), rather than structural (phonological vs visual), data manipulation are quite relevant in the way the child scored differently in the various tasks. Furthermore, M.N. generally displayed average to good ability levels in math calculation, except for oral multiplication and division activities. By way of conclusion, data are discussed in terms of strengths and weaknesses in relation to special learning trajectories in education and the relevant achievements.